Pembelajaran Pendidikan Agama Islam Pada Anak Berkebutuhan Khusus Tunanetra - Aulia Farkhan; Sifa Azahra; Bunga Melati Sukma; Wahyu Ramadan; Difa'ul Husna (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Education To ensure a more dignified life, everyone has a fundamental interest in education. According to Article 31 of the 1945 Constitution, the state is obliged to provide high-quality education services to all its citizens, including those with potential inequalities (disabled). Children with special needs have unique characteristics that distinguish them from other children but do not necessarily exhibit mental, emotional, or physical disabilities. Because of their uniqueness, children with special needs (ABK) require special care. Great children is the first term used to refer to children with special needs in Indonesia. Because some disabilities (children with special needs) and Children with Special Needs have only temporary characteristics, children with special needs include children with special needs that are permanent. Children with special needs are those who struggle to adjust because of trauma, confusion, or difficulty concentrating. With the right help, temporary special needs children can become permanent. Islamic education learning methods have discussed various teaching strategies that educators can use in their classroom activities. In this case, several approaches have been presented, including the lecture method, question and answer, discussion, and giving assignments, among others. Similar to other forms of education, the instructor prepares the necessary tools and media, such as braille, shaped teaching aids, speakers, or other items that can help blind students in learning activities. These materials are ensubywith the lessons to be taughTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//